Implikasi Makanan Haram Terhadap Perkembangan Psikologis Manusia - Said Syaripuddin; Ardi Ardi (Universitas Muslim Indonesia, 2023)
This paper attempts to reveal the criteria for animal meat that is unlawful for consumption in Islam, and the effect of consuming unclean foods on one's psychological development. This paper is a literature review. Using a juridical, maslahat, sociological, and philosophical approach. Sources of information were obtained through the results of a study of the opinions of fiqh scholars in fiqh books, both classical and contemporary, related to the discussion. This paper aims to provide a juridical explanation of the problems of the ummah regarding the criteria for animals whose meat is unclean for consumption in Islam, and the effect of unclean food on a person's psychological development. In the study, it was found that there are various criteria for animals whose meat is forbidden to consume, such as animals that are considered unclean in Islam, animals with fangs, animals (birds) that have long nails to attack their enemies, disgusting animals (insects), animals that are ordered to be killed. , or it is forbidden to be killed in Islam. Based on research conducted by experts, consuming the meat of these animals can have a negative influence on a person's psychological development, for example, having an angry and greedy character like the behavior of wild animals.